ANALYSIS OF EXPLOSIVE ENERGY DISTRIBUTION AT PIT 7 WEST PT. MAKMUR MANDIRI UTAMA BINUNGAN SUARAN - BERAU, EAST KALIMANTAN PROVINCE - Mulya Gusman; Fellya Septia Fauzi; Andree Octova (Puslitbang tekMIRA, 2022)
Blasting geometry and blasting material filling are closely related to the rock mass characteristics and the geological conditions to obtain ideal fragmentation. Blastability Index analysis, including Description of Rock Mass, Combined Plane Spacing, Combined Plane Orientation, Specific Gravity Influencey, and Hardness, are the alternative geometry experiment conducted to overcome the problem of rock fragmentation so that the speed of excavation equipment can increase according to the productivity of Komatsu PC2000 plan at PT. BUMA Jobsite BINSUA. Furthermore, the actual rock values obtained from blasting location and alternative geometry recommendations using R.L.Ash theory combined with Vertical Energy Distribution theory. In the C2 layer with a rock factor value of 5.95, the recommended load is 7.2 m, space is 8.3 m, and the VED explosive power is 48%. In layer D2 the rock factor value is 6.89 with a load of 7.5 m, space of 8.3 m, and 55% VED explosive charge. While in the DU layer, the rock factor value is 6.39 with a load of 7.3 m, 8.4 m space, and 51% VED filling of explosives. Prediction of blasting fragmentation analysis using Kuz-ram theory obtained fragmentation > 100 cm, namely 14.99% for the C2 layer, 14.84% for the D2 layer, and 14.82% for the DU layer.